Maximizing the potential relationship between media and religious beliefs in inspiring positive intentions to register as organ donors - Faerozh Madli; Yuzainy Janin; Shaierah Gulabdin; Jakaria Dasan; Mat Salleh @ Salleh Wahab; Bibianah Thomas (Human Resource Management Academic Research Society (HRMARS), 2024)
When discussing about organ donation, various contexts come to mind for individuals. Most often, what typically comes to mind is the relatively low number of individuals registered as organ donors. The issue of the declining number of organ donors is a topic that has been widely discussed among society. Therefore, based on this ongoing issue, this study focuses on how to address it by maximizing the potential of media and religious beliefs in influencing individuals to develop a positive intention to register as organ donors. This study thoroughly examines both factors and their interrelation in the context of organ donation. The study concludes that these two factors are crucial in influencing individuals to develop a positive intention to register as organ donors. Additionally, the study also emphasizes how these factors dynamically influence the process of forming a positive intention to register as organ donors. The findings of this study have the potential to be leveraged in the future for both social marketing purposes and academic research.